Time-Gating method with automatic calibration for accurate measurements of electrically small antenna radiation patterns in Non-Anechoic environments. (28th February 2023) - Bekasiewicz, Adrian; Koziel, Slawomir; Czyz, Michal
Highlights: Compact antenna measurements are normally performed in expensive test sites. Non-anechoic sites require post-processing to obtain high-fidelity measurements. Data can be refined using inefficient and difficult to set up time-gating method. Low-cost, test-site calibration algorithm for time-gating method (TGM) is proposed. Method improves fidelity and reduces the cost of measurement data acquisition. Abstract: Non-anechoic sites represent a cheap alternative to measurements of antennas in dedicated facilities. However, due to a high noise—from the external EM signal sources and multipath interferences—the quality of radiation patterns obtained in non-anechoic conditions is poor. The characteristics can be corrected using a time-gating method (TGM), which involves filtering of the noise based on temporal analysis of the measured signals. Unfortunately, determination of appropriate TGM setup is prone to failure due to its manual, or semi-manual nature. In this work, an automatic TGM calibration algorithm for accurate measurements in non-anechoic environments has been proposed. The method involves calibration of the test site using the antenna with known accurate responses. The process is implemented as an optimization routine where TGM intervals are adjusted through a curve fitting of the on-site measurements to the reference radiation patterns. The proposed framework has been demonstrated using four compact radiators and validated against the state-of-the-art techniques. Applicability of the method for calibration of the measurements in distinct test sites, as well as the analysis of the aliasing and external noise on the quality of corrected measurements have also been investigated.